2002
DOI: 10.1103/physrevb.66.245301
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent three-dimensional models for quantum ballistic transport in open systems

Abstract: A quasi-three-dimensional model for quantum ballistic transport in nanostructures is proposed. The model goes beyond the Thomas-Fermi approximation and is numerically more tractable than the full threedimensional Schrödinger-Poisson model. Its derivation relies on the strong confinement of electrons at the heterojunction which allows us to split the three-dimensional Schrödinger equation into a one-dimensional Schrödinger equation for the confined direction and a two-dimensional Schrödinger equation in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…The growing interest of the scientific community towards quantum macroscopic models arises from the fact that they are computationally less expensive than microscopic models such as the Schrödinger or Wigner equation [3,4,9,30,32,33]. Simultaneously, collisions can be modeled without the use of quantum collision operators which are difficult to handle.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest of the scientific community towards quantum macroscopic models arises from the fact that they are computationally less expensive than microscopic models such as the Schrödinger or Wigner equation [3,4,9,30,32,33]. Simultaneously, collisions can be modeled without the use of quantum collision operators which are difficult to handle.…”
Section: Introductionmentioning
confidence: 99%
“…2 Our simulator includes a full three-dimensional ͑3D͒ treatment of electrostatics, and is based on real space nonequilibrium Green's function ͑NEGF͒ technique within the nearest neighbor -orbital approximation. 17,18 To model the vacancy, we set the on-site potential to 10 6 eV at the carbon vacancy site, which ensures that a channel electron is effectively repelled from the location of the vacancy. 19 We find that the vacancy creates a localized state in the band gap and a reduction of the transmission probability in both the conduction and valence bands.…”
mentioning
confidence: 99%
“…The potential at the top nsensitive to the local electron charge, and is solely determined by the applied voltage biases found that C G < C Q when V GS > 0.28V so the QCL is not achieved at the the SiO 2 layer [7][8][9][10][11][12]. …”
Section: International Journal Of Advanced Engineering Research and Smentioning
confidence: 99%